1996
DOI: 10.1007/bf00843714
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AIDS-related tuberculosis with concordant gallium-67 and three-hour delayed thallium-201 scintigraphy

Abstract: Concordant gallium-67 and thallium-201 uptake has been described in malignant lesions. More recently, 201Tl accumulation has been described in some benign conditions. The authors report three HIV-positive patients who underwent 67Ga and 201Tl scintigraphy. These studies revealed concordant 67Ga and 201Tl uptake and tumour was erroneously diagnosed. All three patients were finally diagnosed as having tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The differential diagnosis of increased 67Ga uptake includes both infective/inflammatory and malignant processes, and 67Ga alone is thus not specific enough to provide pathognomonic signs for tuberculosis (Bihl and Maier 1987;Dhekne et al 1987;Gomez et al 1996). In tuberculosis associated with AIDS, it is reported that sequential delayed 20ln and 67Ga scintigraphy allows differentiation between infection and malignancy because, in infection, there is clearance of 20lTI on delayed images (Lee et al 1994).…”
Section: Gallium Citrate ( 67 Ga)mentioning
confidence: 96%
See 1 more Smart Citation
“…The differential diagnosis of increased 67Ga uptake includes both infective/inflammatory and malignant processes, and 67Ga alone is thus not specific enough to provide pathognomonic signs for tuberculosis (Bihl and Maier 1987;Dhekne et al 1987;Gomez et al 1996). In tuberculosis associated with AIDS, it is reported that sequential delayed 20ln and 67Ga scintigraphy allows differentiation between infection and malignancy because, in infection, there is clearance of 20lTI on delayed images (Lee et al 1994).…”
Section: Gallium Citrate ( 67 Ga)mentioning
confidence: 96%
“…In a patient with HIV and tuberculous lymphadenopathy, both delayed 20lTI and 67Ga images showed increased uptake. This suggests that caution must be exercised when differentiating between malignancy and infection/ inflammation in HIV-positive patients using delayed 20ln and 67Ga scans, and that careful microbiological and clinical investigation is still necessary to exclude AIDS-related mycobacterial infections (Gomez et al 1996).…”
Section: Gallium Citrate ( 67 Ga)mentioning
confidence: 99%